The "Sting" of Vancouver's Better Housing "Spree", 1919–1949 - Wade, Jill (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1993)
Contrary to other accounts of the 1919 national housing program, this article examines the plan's long-term history using Vancouver as a case study. It argues that a basic structural flaw in the local Better Housing Scheme created financial hardship for the City of Vancouver as well as for mortgagors during the depression. The burden of mortgage repayment that fell to the city discouraged it from participating in other housing initiatives in the 1930s and 1940s. Still, the labour, women's, and veterans' organizations that supported the scheme represented the beginnings of Vancouver's social housing movement that matured in the late 1930s and achieved significant improvements in residential conditions in the 1940s.